2019
DOI: 10.1186/s13104-019-4119-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of matrix-assisted laser desorption ionisation time-of-flight mass spectrometry (MALDI-TOF MS) for the Identification of Group B Streptococcus

Abstract: Objective Group B Streptococcus (GBS) is a leading cause of neonatal meningitis and sepsis worldwide. Intrapartum antibiotics given to women carrying GBS are an effective means of reducing disease in the first week of life. Rapid and reliable tests are needed to accurately identify GBS from these women for timely intrapartum antibiotic administration to prevent neonatal disease. Many laboratories now use matrix-assisted laser desorption ionisation time-of-flight mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
7
0
4
Order By: Relevance
“…Low organism counts or competition from impurities may explain the lower confidence scores in poly-microbial samples. There have been very few studies focusing on the impact of rapid identification from MALDI-TOF MS for both the patient and the laboratory [4,5,[20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Low organism counts or competition from impurities may explain the lower confidence scores in poly-microbial samples. There have been very few studies focusing on the impact of rapid identification from MALDI-TOF MS for both the patient and the laboratory [4,5,[20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical performance of the 179 samples highlights the potential of the CRISPR-GBS assay as a promising assay for the identi cation of GBS, with a clinical sensitivity of 96.64% (144/149, 95% CI = 92.39-98.56%) and a clinical speci city of 100% (30/30, 95% CI = 88.65-100%), compared with the culture-MS method. Culture-MS method as a reference has been con rmed to be more sensitive and speci c than the conventional culture for GBS identi cation [8] [33][34][35]. Moreover, CRISPR-GBS demonstrated a high concordance of 98.88% with the RT-PCR assay.…”
Section: Discussionmentioning
confidence: 99%
“…Lartigue et al reported that MALDI-TOF MS is 100% accurate for the identification of GBS, 27 and other previous studies have also demonstrated it to be a valuable tool for the identification of GBS with a high level of accuracy. [28][29][30][31] Therefore, we strongly believe that the isolated strain was GBS. Furthermore, the serotype of the isolated GBS in the present case was conformed as serotype Ib, using the anti-GBS serotype-specific serum.…”
Section: Discussionmentioning
confidence: 99%